2011
DOI: 10.1093/cercor/bhr026
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Hysterical Blindness

Abstract: The neural mechanisms underlying conversion disorders such as hysterical blindness are at present unknown. Typically, patients are diagnosed through exclusion of neurological disease and the absence of pathologic neurophysiological diagnostic findings. Here, we investigate the neural basis of this disorder by combining electrophysiological (event-related potentials) and hemodynamic measures (functional magnet resonance tomography) in a patient with hysterical blindness before and after successful treatment. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 15 publications
2
24
0
1
Order By: Relevance
“…Artificial stimulation of the intralaminar thalamic sites that are part of the nonspecific system augments visual evoked potentials in response to grating stimuli (Hunsperger and Roman, 1976). Visual, auditory and somatosensory research using recording of brain potentials has repeatedly shown that the level of expression and timing of the negative-polarity potential N1 (with post-stimulus latency equal to about 50–200 ms depending on the modality and stimulation characteristics) strongly correlates with conscious perception (Uttal and Cook, 1964; Wagman and Battersby, 1964; Hassler, 1979; Alter et al, 1990; Cauller and Kulics, 1991; Bachmann, 1994; Imas et al, 2006; Schubert et al, 2006; Schoenfeld et al, 2011; Auksztulewicz et al, 2012; Auksztulewicz and Blankenburg, 2013; Sinke et al, 2014; Pitts et al, submitted). For example, while early post-stimulus potential components are more or less invariant between sleep or sedation on the one hand and awake conditions on the other hand (or even increased in sedation – Imas et al, 2006), N1 is considerably suppressed in the unconscious state.…”
Section: Two Mutually Interacting Brain Systems Related To Consciousnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial stimulation of the intralaminar thalamic sites that are part of the nonspecific system augments visual evoked potentials in response to grating stimuli (Hunsperger and Roman, 1976). Visual, auditory and somatosensory research using recording of brain potentials has repeatedly shown that the level of expression and timing of the negative-polarity potential N1 (with post-stimulus latency equal to about 50–200 ms depending on the modality and stimulation characteristics) strongly correlates with conscious perception (Uttal and Cook, 1964; Wagman and Battersby, 1964; Hassler, 1979; Alter et al, 1990; Cauller and Kulics, 1991; Bachmann, 1994; Imas et al, 2006; Schubert et al, 2006; Schoenfeld et al, 2011; Auksztulewicz et al, 2012; Auksztulewicz and Blankenburg, 2013; Sinke et al, 2014; Pitts et al, submitted). For example, while early post-stimulus potential components are more or less invariant between sleep or sedation on the one hand and awake conditions on the other hand (or even increased in sedation – Imas et al, 2006), N1 is considerably suppressed in the unconscious state.…”
Section: Two Mutually Interacting Brain Systems Related To Consciousnessmentioning
confidence: 99%
“…When similar monocular textures fuse into subjectively visible images, conspicuous occipitally recorded negative component is present, but absent when fusion into visibility is not achieved (Fahrenfort et al, 2012). Moreover, recently it was shown that whether subjective experience of a visual stimulus in hysterical blindness is present or not is reflected in the amplitude of N1 (Schoenfeld et al, 2011). Importantly, while N1 appeared as an authentic NCC, fMRI recording data could not differentiate between consciously seen vs unseen stimuli.…”
Section: Two Mutually Interacting Brain Systems Related To Consciousnessmentioning
confidence: 99%
“…A few brain-imaging studies have examined conversion deficits affecting other neurological functions such as somatosensory loss [35,53], visual loss [9,85,109], or memory loss [33,55,98]. In most cases, reduced activity was observed in brain areas involved in the impaired functions, including somatosensory cortices, occipital lobe, or temporal lobe, respectively (for review see [104,105]).…”
Section: Neuroimaging Findings In Non-motor Conversion Disordersmentioning
confidence: 99%
“…Although there are only a few studies on the role of biological factors in CD, some recent publications report a possible pathology in the cerebral functions of these patients [4][5][6][7]. These studies have mostly been carried out in the subtype of CD with motor signs and are associated with hemispheric dominance, event-related evoked potentials, structural and functional brain imaging and neuropsychological tests (NPT).…”
Section: Introductionmentioning
confidence: 99%